Coastal Sediments 2019 2019
DOI: 10.1142/9789811204487_0015
|View full text |Cite
|
Sign up to set email alerts
|

Drowned Foredune Ridges as Evidence of Pre- Historical Barrier-Island State Changes Between Migration and Progradation

Abstract: The processes driving barrier-island state changes between erosion/migration and growth/progradation are poorly understood. Stratigraphic and chronologic data are used to infer past state changes of Cedar Island, VA, USA. These data indicate that Cedar Island formed seaward of its present position approximately 5000-6000 years ago. Following a period of net landward migration, the north-central section of the island was breached prior to ca. 450 years ago. During this time, an extensive flood tidal delta was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Despite an improved representation of coastal processes such as inlet dynamics, BRIE does not yet aim to simulate the dynamics of any particular barrier system. To do that, we would need to incorporate additional factors such as variations in the coastal lithology and topography (Cooper et al, ; Schwab et al, ; Shawler et al, ; Swanson et al, ), human influence (Oost et al, ), and/or the extent of the marsh platform (Lorenzo‐Trueba & Mariotti, ), which can potentially lead to complex dynamics in the barrier system. For example, paleovalleys can constrain inlet migration rates, and even anchor inlets in place over geological timescales (Beets & van der Spek, ; Mallinson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite an improved representation of coastal processes such as inlet dynamics, BRIE does not yet aim to simulate the dynamics of any particular barrier system. To do that, we would need to incorporate additional factors such as variations in the coastal lithology and topography (Cooper et al, ; Schwab et al, ; Shawler et al, ; Swanson et al, ), human influence (Oost et al, ), and/or the extent of the marsh platform (Lorenzo‐Trueba & Mariotti, ), which can potentially lead to complex dynamics in the barrier system. For example, paleovalleys can constrain inlet migration rates, and even anchor inlets in place over geological timescales (Beets & van der Spek, ; Mallinson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This is exemplified by formerly and presently wide barrier islands such as Cedar and Parramore islands in Virginiaboth of which were historically around 4 times wider than the 400 m wide barrier initialized in our model investigation. Despite experiencing an acceleration in relative SLR of 3 to 4 mm yr −1 over the last century (Boon and Mitchell, 2015), these islands have recently or historically sustained kilometer-scale landward shoreline migration over decadal to centennial timescales (McBride et al, 2015;Deaton et al, 2017;Shawler et al, 2019). Similar longer-term and sustained narrowing of previously wide barriers has also been inferred at Bogue Banks, North Carolina, a system of formerly progradational islands that began to undergo net shoreline erosion at approximately 1 ka (Timmons et al, 2010).…”
Section: Sediment Availability and Relative Sea-level Risementioning
confidence: 60%
“…While the latter is a cross-shore construct based on wave energy, Hallermeier (1978) describes the littoral zone as being significantly shaped by alongshore transport, a process which at least one study has shown can cause upper-shoreface profiles to depart significantly from cross-shore equilibrium predicted by the Bruun rule (List et al, 1997). Similarly, historical and geological investigations indicate that barriers subjected to kilometer-scale shoreline movement over multidecadal timescales are strongly influenced by spatiotemporal variations in alongshore sediment delivery (Brooke et al, 2008;Lindhorst et al, 2010;Oliver et al, 2017;Raff et al, 2018;Shawler et al, 2019).…”
Section: Sandy-substructure Accommodationmentioning
confidence: 99%
See 2 more Smart Citations